The role of information and communication technology (ICT) in the relationship between information asymmetry and financial development: New evidence based on the PSTR model; El papel de las tecnologías de la información y la comunicación (TIC) en la relación entre asimetría de la información y desarrollo financiero: Nuevas pruebas basadas en el modelo PSTR - Mahdieh Rezagholizadeh; Majid Aghaei; Atefeh Alipour Kebria (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
Information and communications technology (ICT) has potential to complement information sharing bureaus (ISB) (private credit bureaus (PCB) and public credit registries (PCR)) in lessening information asymmetry (IA) to enhance financial development. Using ICT as the transition variable, this research employs the panel smooth transition regression (PSTR) model to examine the influence of IA on financial development in 33 least developed countries (LDCs) over the 2000-2021. Results indicate that IA and financial development have a nonlinear nexus and ICT alters this relationship. Based on the findings, this impact has dynamic characteristics of threshold and gradual changes and ICT plays a considerable part in this relationship. When ICT is below the threshold value, that is in the low regime, PCR has a negative impact on financial development. In contrast, when the ICT outstrips the threshold, that is in the high regime, the coefficient is positive. It means that the negative effect of PCR on financial development is offset and even changed into positive as ICT increases. On the other hand, PCB has a positive impact on financial development in both low and high ICT regime. With the transfer from the ICT threshold, the favorable impact of PCB on reducing IA in the direction of financial development grows. The hidden implication is that PCR and PCB (with decreasing IA) promote the financial development, when ICT is at a high level. In other words, ICT could complement the characteristics of PCR and PCB to reduce IA and increase financial development.
Keywords: E44; G00; L86; D82; 330; Information and Communication Technology (ICT); Financial Development; Information Asymmetry (IA); Information Sharing Bureaus (ISB); Panel Smooth Transition Regression (PSTR)